Strategi Pemasaran UMKM di Desa Lubuk Enau Melalui Media Banner dan Google Maps - Chandra, Icha; Rizki, Sutra Meilani; Hakim, Malik; Ningrum, Ayu Lestari Setia; Karaihandak, Wiradinata; Pebriani, Reny Aziatul; Hildayanti, Siti Komariah; Kospa, Herda Sabriyah Dara (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
This Thematic Real Work Lecture (KKN) aims to help Micro, Small and Medium Enterprises (MSMEs) in Lubuk Enau Village in improving marketing strategies through the use of Banner Media and Google Maps. MSMEs in this village face challenges in reaching a wider market due to limited accessibility and lack of knowledge about digital marketing technology. Therefore, the KKN team took the initiative to introduce and implement two promotional media that could significantly increase business visibility. Through this activity, the KKN team provides training and assistance to MSMEs on how to design and install effective banners, as well as how to register and optimize their business locations on Google Maps. The KKN team successfully provided training and mentoring to 31 MSMEs, which resulted in increased business visibility through the installation of attractive banners and location registration on Google Maps. The enthusiasm of MSME actors for digital marketing increased, which is expected to strengthen relationshio with consumers and support local economic growth. This activity is an example of the implementation of a marketing strategy that can be adopted by other villages with similar characteristics.